Dynamic Blood Concentrations of Aβ1–40 and Aβ1–42 in Alzheimer’s Disease - Yuan-Han Yang; Yuan-Han Yang; Yuan-Han Yang; Yuan-Han Yang; Yuan-Han Yang; Ling-Chun Huang; Ling-Chun Huang; Sun-Wung Hsieh; Sun-Wung Hsieh; Li-Ju Huang; Li-Ju Huang (Frontiers in Cell and Developmental Biology, 2020)
Amyloid-beta (Aβ) is produced by the cleavage of amyloid precursor proteins in the cell membrane by β-secretase and γ-secretase into a monomeric form with peptides of different lengths such as Aβ1–40 or Aβ1–42, which is then transformed into oligomeric and fibril forms and is considered to be one of the hallmarks of Alzheimer’s disease (AD). The plasma concentrations of Aβ1–40 and Aβ1–42 are unstable after blood samples have been obtained. In order to examine the dynamic changes of plasma Aβ1–42 and Aβ1–40 in blood samples, we used fresh blood samples in ethylenediaminetetraacetic acid tubes from 32 clinically diagnosed AD patients. Each sample was subdivided into eight sub-samples, and levels of Aβ1–40 and Aβ1–42 were measured at 0 (baseline), 0.5, 1, 2, 3, 5, 8, and 24 h, respectively. All samples were incubated at 37°C before being measuring. The results showed that compared to baseline, 87.5 and 62.5% of the patients had higher plasma levels of Aβ1–42 and Aβ1–40 at 24 h, respectively. The patients with an increased amyloid level did not have a significantly different apo-lipoprotein E4 allele (APOE4) gene status for either Aβ1–40 (p = 0.422) or Aβ1–42 (p = 1.000). However, for plasma Aβ1–42, the APOE4 carriers had a significantly lower level than the non-carriers at baseline [31.2 ± 6.5 (mean ± SD) ng/ml vs. 50.4 ± 47.7 ng/ml, p = 0.031] and 0.5 h (37.5 ± 7.6 ng/ml vs. 51.9 ± 30.8 ng/ml, p = 0.043). There were no significant differences between the APOE4 carriers and non-carriers in plasma Aβ1–42 concentration at 1, 2, 3, 5, 8, and 24 h (p = 0.112, p = 0.086, p = 0.112, p = 0.263, p = 0.170 and p = 0.621, respectively). The Aβ1–40 level was related to disease severity as assessed using the clinical dementia rating (CDR) scale. Patients with advanced stages of dementia (CDR = 1 and CDR = 2) had a significantly higher Aβ1–40 level compared to those with very mild stage dementia (CDR = 0.5) at all time points (p < 0.05) except for 24 h (p = 0.059). Our findings illustrate the effects of APOE4 status on dynamic changes in plasma Aβ1–40 and Aβ1–42 levels, and significant associations between Aβ1–40 level and disease severity. Further studies are needed to investigate the exact mechanisms of how APOE4 affects the dynamic changes in plasma Aβ1–40 and Aβ1–42, and the association between Aβ1–40 and advanced dementia.